AS REPRESENTAÇÕES SOCIAIS DA IDENTIDADE DOCENTE: COM A PALAVRA OS PROFESSORES DO PROFEBPAR/UFMA - LIMA, Sueli Sousa (2016)
This paper aims to analyze the contributions of the PROFEBPAR / UFMA Pedagogy course of Vargem Grande - MA in the construction of teacher - student identity in light of the Social Representation Theory - TRS. It is based on the theoretical reference of social representations, because it favors the comprehension of the object in its integrality. The discussion here is of a qualitative approach, without disregarding the quantitative data. It considers the presuppositions of this approach, as an act of communication between subjects, in which intersubjectivity, interaction, affections and spontaneity between the researcher and the subjects of the research also come into play. In order to analyze the data collected, Bardin (1977, 2007) and Bonfim (2008) use the technique of content analysis, which, when conducting systematic, qualitative or quantitative descriptions, helps to reinterpret the messages and to achieve An understanding of meanings at a level that goes beyond a common reading. In order to understand the thematic of this study, we mainly use the following theoretical reference: teacher training: Cury (1996), Tanuri (2000), Freitas (2002, 2006), Gatti and Barreto (2009), Melo; Birth (2013), etc .; (1998), Jodelet (1989, 1993, 2001), Jovchelovitch (2000, 2008), Guareschi (1996), Bonfim (2007), among others ; And identity processes: Nóvoa (1992), Ciampa (1997); Dubar (2005, 2007), Deschamps; Moliner (2009). In this way, initially, it focuses on teacher education in Brazil, with emphasis on emergency programs, since the history of this training contributes to the construction of teacher identities. The research subjects are 20 (twenty) professors-students of the Pedagogy course of PROFEBPAR / UFMA of Vargem Grande - MA. From the Technique "Who Am I? Applied, he / she realizes that the predominant answers indicate that the majority of the participants of the research consider teacher, cheerful and friend than it is inferred that the course of Pedagogy has contributed positively so that the subjects incorporate the teaching in its academic formation. Thus, it is understood that the elements: teacher, joy and friendship are part of the construction of the teaching identity of the teacherstudents of the course under analysis. The content analysis allowed the systematization of the data collected through a profile questionnaire, semi-structured interviews and the understanding of the object of study. It was possible, therefore, to list three Thematic Units for our research: I am a teacher, yes; Learning in training; And PROFEBPAR / UFMA in all this. Through these units are evidenced many processes involved in the constitution of the teacher identity, from those related to the personal history of each one, such as, for example, childhood experiences, jokes or experiences with teachers - aspect of the biographical axis, therefore, involves More subjective transactions - to actual experiences of professional practice and training practices, especially involving supervised internships and didactic experiences. Thus, the study suggests expanding the debate about the construction of the identity of teachers-students in undergraduate courses.